Pessoas idosas vivendo com HIV em Goiás: um estudo de gênero, sexualidade e subjetividades - Andrade, Márcia Andréa Rodrigues (2017)
This thesis is about aging, HIV and gender in the context of subjectivity. In a first moment, it looks to the importance of aging for the sociological studies, as well to the formation of the categories of elderly people and people living with HIV. Then, it analyses the subjectivity of elderly people. For doing that, a qualitative sociological research and a bibliographical review of authors who explore the topic were realized. It was possible to point out the limits of the discursive construction of the erotization process of the old age, in a critique of the gerontological discourse of multisensorial sexuality as well of the discourse of HIV feminization. To go deep in the debate, the thesis explores the idea of biographical rupture, which proposes a reordering of the everyday life. By understanding subjectivity through biographical ruptures, it was possible to dialogue with the logic of affective, marital and family experiences, the way of facing HIV, stigmas, secrets, corporeity and sexuality, bringing the unequal gender relations to the debate. The empirical analysis of these questions relies on field work and interviews, done between October 2014 and June 2015 with 15 elderly people over 60 years of age who receive regular treatment at the Hospital of Tropical Diseases Dr. Anuar Auad, in Goiânia, Brazil. The thesis concludes that old age and the way of facing HIV are heterogeneous. The unequal gender relations exercise a fundamental role in the subjectivity, since they produce different reactions to risk, marital life and the way how elderly people face HIV, which leads to a reflection about the production of differences. The living experience with HIV has given to the interviewees a constant learning for the recognition and reordering of the life ruptures. The understanding of the thesis is that the dilemmas of elderly people living with HIV are not individuals, but a responsibility of all the society.